In vitro and in vivo antileishmanial activity of Artemisia annua L. leaf powder and its potential usefulness in the treatment of uncomplicated cutaneous leishmaniasis in humans (2017)
ABSTRACT: Introduction: Cutaneous leishmaniasis (CL) is a tropical disease that affects millions of individuals worldwide. The current drugs for CL may be effective but have serious side effects; hence, alternatives are urgently needed. Although plant-derived materials are used for the treatment of various diseases in 80% of the global population, the validation of these products is essential. Gelatin capsules containing dried Artemisia annua L. leaf powder were recently developed as a new herbal formulation (totum) for the oral treatment of malaria and other parasitic diseases. Here, we aimed to determine the usefulness of A. annua gel capsules in CL. Methods: The antileishmanial activity and cytotoxicity of A. annua L. capsules was determined via in vitro and in vivo studies. Moreover, a preliminary evaluation of its therapeutic potential as antileishmanial treatment in humans was conducted in 2 patients with uncomplicated CL. Results: Artemisia annua L. capsules showed moderate in vitro activity in amastigotes of Leishmania (Viannia) panamensis; no cytotoxicity in U-937 macrophages or genotoxicity in human lymphocytes was observed. Five of 6 (83.3%) hamsters treated with A. annua capsules (500mg/kg/day) for 30 days were cured, and the 2 examined patients were cured 45 days after initiation of treatment with 30g of A. annua L. capsules, without any adverse reactions. Both patients remained disease-free 26 and 24 months after treatment completion. Conclusion: Capsules of A. annua L. represent an effective treatment for uncomplicated CL, although further randomized controlled trials are needed to validate its efficacy and safety.